2004
DOI: 10.1029/2003gl018680
|View full text |Cite
|
Sign up to set email alerts
|

Thawing sub‐arctic permafrost: Effects on vegetation and methane emissions

Abstract: [1] Ecosystems along the 0°C mean annual isotherm are arguably among the most sensitive to changing climate and mires in these regions emit significant amounts of the important greenhouse gas methane (CH 4 ) to the atmosphere. These CH 4 emissions are intimately related to temperature and hydrology, and alterations in permafrost coverage, which affect both of those, could have dramatic impacts on the emissions. Using a variety of data and information sources from the same region in subarctic Sweden we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
480
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 479 publications
(499 citation statements)
references
References 21 publications
17
480
0
2
Order By: Relevance
“…In northern Sweden, we have previously documented dramatic ecosystem changes as a consequence of the ongoing permafrost thaw (Christensen et al 2004;Johansson et al 2006). A substantial change in the surface hydrology follows the palsa degradation and subsequent increases in CH 4 emissions (Christensen et al 2004) but also in the CO 2 sink strength at the landscape scale has been documented (Johansson et al 2006).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In northern Sweden, we have previously documented dramatic ecosystem changes as a consequence of the ongoing permafrost thaw (Christensen et al 2004;Johansson et al 2006). A substantial change in the surface hydrology follows the palsa degradation and subsequent increases in CH 4 emissions (Christensen et al 2004) but also in the CO 2 sink strength at the landscape scale has been documented (Johansson et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…These exchanges are intimately related to temperature and hydrology, and alterations in permafrost coverage, which affect both of those, could have dramatic impacts on the combined climate forcing from these exchanges. Recent studies have shown that palsa mire ecosystems in Sweden are subject to dramatic changes in the distribution of permafrost and vegetation (Christensen et al 2004;Malmer et al 2005;Johansson et al 2006) and also that this is a general phenomenon at least for most of northern Scandinavia (Bosiö et al 2012). These changes are most likely caused by a warming that has been observed during recent decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation of the area is characterized by a mosaic of subarctic birch forests and wetlands while above the tree line fjäll tundra ecosystems dominate [Malmer et al, 2005]. Various studies report the influence of climate change on the Stordalen mire vegetation [Christensen et al, 2004;Malmer et al, 2005;Svensson et al, 1999], however, there is little known about the local aerosol properties [Svenningsson et al, 2008]. It is expected that depending upon wind direction and meteorology particulate sources from both natural (e.g., oceanic and boreal forest) and anthropogenic (e.g., the port at Narvik and industries on the Barents Sea) sources are expected to perturb the background conditions .…”
Section: Sampling Sitementioning
confidence: 99%
“…In subarctic Fennoscandia, permafrost mires are currently subjected to climate related thawing (Åkerman and Johansson 2008;Callaghan et al 2012) and shift in vegetational and hydrological patterns (Malmer et al 2005;Bosiö et al 2012). These changes exert a significant impact on atmospheric CO 2 sink function and CH 4 emissions (Christensen et al 2004;Johansson et al 2006) and on soil hydrologic dynamics (O'Donnell et al 2012;Jorgenson et al 2013).…”
Section: Introductionmentioning
confidence: 99%